EFISIENSI PERSAINGAN BANK UMUM SYARIAH: PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) DAN BOSTON CONSULTING GROUP (BCG) - Rizqon Halal Syah Aji (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
Islamic Banking industry in Indonesia has begun dynamic. Product availability and standardization of Islamic banking products, the level of understanding by the public of products of Islamic banks and human resources. Market share of Islamic Banking in Indonesia to lock everything. Recent data Directorate of Islamic Banking in 2011 reached Rp 127,19 T, assets of BPRS amounting to Rp 3.35 T, can be calculated total Islamic banking assets as of October 2011 reached Rp 130,5 T. Financing very important factor, Data Envelopment Analisys (DEA) is a measuring instrument of financing. Map of the Bank's performance in the competition between banks can be analyzed by matrix BCG (Boston Consulting Group). This matrix is used to describe the difference between the position of the relative market share of the Bank.DOI: 10.15408/sjie.v3i1.2059